Prayers for sale: lived Islam and spiritual marketplace in contemporary Nigerian society - Mudasiru, Moruff (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
Prayers play a significant role in the pursuit of a spiritual culture that fosters the social fabric of everyday life in a spiritual marketplace. Many people increasingly embrace Islam and Muslim clerics because they wield significant spiritual capital, often influenced by neoliberal ideology. Nevertheless, limited scholarly attention is devoted to these expressive cultural practices as it is lived. This study examines how itinerant Muslim clerics in Yoruba society creatively market and deliver prayers in public spaces and explores the socio-religious functions these practices fulfil in contemporary urban contexts. The research explores the material and embodied power inherent in Islamic symbolism by focusing on clerics who publicly offer prayers and blessings as a means to soothe and respond to the complexities of human existence. Utilising performance theory as its analytical framework, and drawing on ethnographic fieldwork conducted in southwest Nigeria, the study explores how the commodification of prayers is mobilised to shape urban life. It further investigates the ritualised pursuit of baraka (divine blessing) among religious consumers aiming to attain personal goals, most notably success, hope, survival, and livelihood. These salient yet creative practices illustrate how the Yoruba people construct and ‘live’ to create a reflective spiritual lifestyle that embeds Islamic sensibilities and meanings within the broader socio-cultural landscape of everyday urban life.